Health system effects of implementing integrated community case management (iCCM) intervention in private retail drug shops in South Western Uganda: a qualitative study. (13th September 2017) - Kitutu, Freddy Eric; Mayora, Chrispus; Johansson, Emily White; Peterson, Stefan; Wamani, Henry; Bigdeli, Maryam; Shroff, Zubin Cyrus
Abstract : Background: Intervening in private drug shops to improve quality of care and enhance regulatory oversight may have health system effects that need to be understood before scaling up any such interventions. We examine the processes through which a drug shop intervention culminated in positive unintended effects and other dynamic interactions within the underlying health system. Methods: A multifaceted intervention consisting of drug seller training, supply of diagnostics and subsidised medicines, use of treatment algorithms, monthly supervision and community sensitisation was implemented in drug shops in South Western Uganda, to improve paediatric fever management. Focus group discussions and in-depth interviews were conducted with stakeholders (drug sellers, government officials and community health workers) at baseline, midpoint and end-line between September 2013 and September 2015. Using a health market and systems lens, transcripts from the interviews were analysed to identify health system effects associated with the apparent success of the intervention. Findings: Stakeholders initially expressed caution and fears about the intervention's implications for quality, equity and interface with the regulatory framework. Over time, these stakeholders embraced the intervention. Most respondents noted that the intervention had improved drug shop standards, enabled drug shops to embrace patient record keeping, parasite-based treatment of malaria and appropriate medicine use. There was also improved supportive supervision, and better compliance to licensing and other regulatory requirements. Drug seller legitimacy was enhanced from the community and client perspective, leading to improved trust in drug shops. Conclusion: The study showed how effectively using health technologies and the perceived efficacy of medicines contributed to improved legitimacy and trust in drug shops among stakeholders. The study also demonstrated that using a combination of appropriate incentives and consumer empowerment strategies can help harmonise common practices with medicine regulations and safeguard public health, especially in mixed health market contexts.